2019
DOI: 10.1186/s13063-019-3179-9
|View full text |Cite
|
Sign up to set email alerts
|

CARer-ADministration of as-needed subcutaneous medication for breakthrough symptoms in homebased dying patients (CARiAD): study protocol for a UK-based open randomised pilot trial

Abstract: BackgroundWhile the majority of seriously ill people wish to die at home, only half achieve this. The likelihood of someone dying at home often depends on the availability of able and willing lay carers to support them.Dying people are usually unable to take oral medication. When top-up symptom relief medication is required, a clinician travels to the home to administer injectable medication, with attendant delays. The administration of subcutaneous injections by lay carers, though not widespread practice in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…132 Such practices remain uncommon in the UK, with only a small body of exploratory work and local policy having been developed to date. [133][134][135][136] The prescribing and subsequent use of AMs is a very significant moment in the patient's dying trajectory.…”
Section: Anticipatory Prescribingmentioning
confidence: 99%
See 2 more Smart Citations
“…132 Such practices remain uncommon in the UK, with only a small body of exploratory work and local policy having been developed to date. [133][134][135][136] The prescribing and subsequent use of AMs is a very significant moment in the patient's dying trajectory.…”
Section: Anticipatory Prescribingmentioning
confidence: 99%
“…Other participants were willingsometimes keento extend their role in managing medicines and learn techniques of administration, such as giving injections, administering AMs, replacing syringe driver cartridges or managing dialysis. 112,133 Taking a proactive role could be valued as a means of providing rapid pain relief and reducing dependence on HCPs. FCGs could be frustrated when professionals did not acknowledge their competence and expertise.…”
Section: Risk and Responsibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Trainings for lay carers, for example for subcutaneous as-needed doses, may reportedly play a key role in achieving adequately symptom controlled home deaths. 33 Additionally, previous studies have suggested educational training as well as simulation programs for professionals, especially regarding types of sedation that are only rarely performed. 21 , 34 In accordance with a previous study, our participants also stressed the value of shared documentation involving all relevant parties.…”
Section: Discussionmentioning
confidence: 99%
“…Prescribers are now being asked to consider drug administration by family caregivers when community nurses and doctors are not available to administer end of life drugs in a timely way 123. Family caregivers willing to take on this role should be adequately trained and responsively supported with access to 24 hour phone advice 3789…”
mentioning
confidence: 99%